Poland’s Chairmanship in the Organization for Security and Co-operation in Europe in 2022: Objectives and Their Implementation in the Face of the Russian-Ukrainian War - Dulak, Michał (2025)
Poland’s Chairmanship in the Organization for Security and Cooperation in Europe in 2022 took place during an unprecedented crisis— Russia’s full-scale invasion of Ukraine. This book provides a comprehensive analysis of Poland’s OSCE Chairmanship, assessing both its diplomatic efforts and the broader challenges facing the organization.The first part of the book examines the evolution of the OSCE, its institutional weaknesses, and its ability to respond to contemporary security threats. It critically evaluates the OSCE’s engagement in Ukraine since 2014, including the Special Monitoring Mission and Trilateral Contact Group, exposing the organization’s structural limitations in conflict resolution.The second part focuses on Poland’s leadership in the OSCE, detailing how its initial objectives were reshaped by war. It explores Poland’s strategic decisions, such as implementing the “no business as usual” policy and launching the OSCE Support Programme for Ukraine. The book concludes with a discussion on the future of the OSCE, questioning whether institutional reforms are necessary to prevent authoritarian states from obstructing its mission.A must-read for scholars, diplomats, and policymakers, this publication offers critical insights into European security governance, Poland’s diplomatic strategy, and the OSCE’s role in a rapidly changing geopolitical landscape.